Implementasi Peraturan Pemerintah Nomor 30 Tahun 2019 Tentang Penilaian Kinerja PNS di Sekretariat Daerah, Subulussalam - Abdul Rajab; Heri Kusmanto; Adam Adam (Mahesa Research Center, 2022)
This study aims to determine and analyze the implementation of the Government Regulation of the Republic of Indonesia Number 30 of 2019 concerning the Performance Assessment of Civil Servants and the obstacles in the Regional Secretariat of Subulussalam City Government. This study uses a descriptive method with a qualitative approach. This research is described descriptively with a juridical approach to public administration. The data collection techniques in this study are Primary Data Collection, through interviews (interviews), observations and documentation and Secondary Data Collection, with literature study. The data analysis technique consists of three streams of activities that occur simultaneously, namely: data reduction, data presentation, conclusion drawing/verification. The results showed that the implementation of PP no. 30 of 2019 concerning the Performance Assessment of Civil Servants has not been fully implemented yet. Implementation has been successfully implemented in terms of communication and bureaucratic structure, but has not been successful in terms of resources and disposition. The obstacles faced are the appraiser (superior) is not able to control the view of the proximity element in assessing the work of subordinates, employees often make excessive reports, and the provision of disciplinary sanctions is still relatively indecisive.